Chemokine Receptor 2-Mediated Accumulation of Fungicidal Exudate Macrophages in Mice That Clear Cryptococcal Lung Infection - Osterholzer, John J. (American Society for Investigative Pathology, 2011)
Clearance of pulmonary infection with the fungal pathogen Cryptococcus neoformans is associated with the accumulation and activation of lung macrophages. However, the phenotype of these macrophages and the mechanisms contributing to their accumulation are not well-defined. In this study, we used an established murine model of cryptococcal lung infection and flow cytometric analysis to identify alveolar macrophages (AMs) and the recently described exudate macrophages (ExMs). Exudate macrophages are distinguished from AMs by their strong expression of CD11b and major histocompatibility complex class II and modest expression of costimulatory molecules. Exudate macrophages substantially outnumber AMs during the effector phase of the immune response; and accumulation of ExMs, but not AMs, was chemokine receptor 2 (CCR2) dependent and attributable to the recruitment and subsequent differentiation of Ly-6C(high) monocytes originating from the bone marrow and possibly the spleen. Peak ExM accumulation in wild-type (CCR2(+/+)) mice coincided with maximal lung expression of mRNA for inducible nitric oxide synthase and correlated with the known onset of cryptococcal clearance in this strain of mice. Exudate macrophages purified from infected lungs displayed a classically activated effector phenotype characterized by cryptococcal-enhanced production of inducible nitric oxide synthase and tumor necrosis factor α. Cryptococcal killing by bone marrow–derived ExMs was CCR2 independent and superior to that of AMs. We conclude that clearance of cryptococcal lung infection requires the CCR2-mediated massive accumulation of fungicidal ExMs derived from circulating Ly-6C(high) monocytes.